Emergence of coinfection with visceral Leishmania infantum in COVID-19 patients: a case‒control field study in an endemic area of visceral leishmaniasis in Iran - Selva Aminizadeh; Behnam Mohammadi-Ghalehbin; Mehdi Mohebali; Homa Hajjaran; Zabih Zarei; Zahra Heidari; Behnaz Akhondi; Zahra Alizadeh; Jafar Aghaei (BMC Infectious Diseases)
Abstract Background COVID-19 is a pandemic involving coinfection with other opportunistic microorganisms, including parasites such as Leishmania infantum. The present study aimed to determine the frequency of L. infantum infection and its role in disease and mortality among symptomatic COVID-19 patients in comparison with the non-COVID-19 control group in the endemic area of visceral leishmaniasis (VL) in Iran. Methods A total of 250 blood samples from hospitalized COVID-19 patients and 231 blood samples from non-COVID-19 patients as a control group were collected in Mashkin Shahr city, Iran from October 2020 to May 2021, and anti-Leishmania infantum antibodies were detected via direct agglutination test (DAT). For confirmation of non-COVID-19 samples as the control group, anti-COVID-19 IgG antibodies were measured via indirect ELISA. Additionally, demographic data, clinical data, and disease outcomes were recorded. Results Overall, 46 (18.4%) COVID-19 patients and 18 (7.8%) non-COVID-19 patients had anti-Leishmania infantum antibodies at titers of 1:200 or higher according to the DAT (p value $$\:<$$ 0.05). In the COVID-19 group, there was no statistically significant association between coinfection with L. infantum and sex, residency, treatment outcome, or symptoms. Conclusion The results of this study revealed that the overall seroprevalence of L. infantum infection among patients with COVID-19 was 2.66 times greater than that in the control group, which was statistically significant. It seems that L. infantum infection can be considered a risk factor for COVID-19, particularly in VL endemic areas. Clinical trial number Not applicable.